1987
DOI: 10.1002/hed.2890090506
|View full text |Cite
|
Sign up to set email alerts
|

Completion thyroidectomy for thyroid carcinoma

Abstract: We have reviewed the charts of 149 patients who underwent completion thyroidectomies for cancer of the thyroid. The purpose of the study was to evaluate extent of residual disease in the thyroid, and morbidity and mortality of the operation. Residual cancer was found in 58% of the cases, the morbidity was low, and there was no operative mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Papillary thyroid cancer is known to be multifocal in about 30–80% (Rao et al ., 1987; Auguste & Attie, 1990; Pacini et al ., 2001), thus initial total thyroidectomy remains an effective and safe treatment method to reduce the surgical risk of the patients and facilitate to perform radioactive iodine therapy. Follicular thyroid cancer tends to be less multifocal than papillary thyroid cancer does but they are much more aggressive and, if they are widely invasive or extrathyroidal disease is found, completion thyroidectomy should also be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Papillary thyroid cancer is known to be multifocal in about 30–80% (Rao et al ., 1987; Auguste & Attie, 1990; Pacini et al ., 2001), thus initial total thyroidectomy remains an effective and safe treatment method to reduce the surgical risk of the patients and facilitate to perform radioactive iodine therapy. Follicular thyroid cancer tends to be less multifocal than papillary thyroid cancer does but they are much more aggressive and, if they are widely invasive or extrathyroidal disease is found, completion thyroidectomy should also be performed.…”
Section: Discussionmentioning
confidence: 99%
“…The concerns about increased morbidity with more than a thyroid lobectomy are not necessarily justified. Irl experienced hands, total thyroidectomy, and more importantly secondary thyroid operations, can be performed safely with little morbidity to the patient [9,13,24,25,27,34]. Calabro and coworkers,[24] in a recent review of completion thyroidecto" mies, reported an incidence of transient hypocalcemia of 129~ and transient RLN palsy of 1.5%.…”
Section: Discussionmentioning
confidence: 99%
“…The complication rates of surgery, laryngeal nerve injury, and hypoparathyroidism are the main reason to choose lobectomy in DTC patients with primary tumor size ≤1 cm [13, 14]. However, in the hands of an experienced thyroid surgeon, the complication rate of total thyroidectomy is as low as 2% while the incidence of recurrent laryngeal nerve palsy is increased in cases of reoperation for recurrences in the contralateral lobe [1517].…”
Section: Discussionmentioning
confidence: 99%